A cloudy conundrum. - Woo, Ying Yong. (2010)
A Cloudy Conundrum: “Up above among the skies, there live creatures which create clouds for weather while hiding from humans. However, one day, a by-plane crashes onto the outskirts of their city. They are rushing against time to hide their city before the pilot reaches it in his exploration of this strange new world. Now, if only they can convince him that he is in a believable heaven. But of course, things never happen the way you want them to.”